ChemInform Abstract: Gold‐Catalyzed Cyclization Leads to a Bridged Tetracyclic Indolenine that Represses β‐Lactam Resistance. Issue 51 (December 2015) - Xu, Wenqing; Wang, Wei; Wang, Xiang
Abstract: Tricyclic N‐heterocyclic substrates silylated at the indole nitrogen are found to be optimal for the cyclization process.